Development of E-LKPD Assisted by the Flip Builder Application with a Discovery Learning Approach on Business and Energy Materials - Aris, Mulki; Sakdiah, Halimatus; Idris, Syafrizal; Ginting, Fajrul Wahdi; Safriana, Safriana (Universitas Islam Negeri Ar-Raniry, 2025)
The learning process in general still uses books and conventional learning models that make students feel bored and bored. The objectives of the study were to: (1) determine the feasibility of E-LKPD, (2) find out the response of students to E-LKPD, (3) find out the improvement of student learning outcomes to E-LKPD based on discovery learning. The method used in the research is the research method of research and development (R & D) development with a 4-D model. The results showed that: (1) the feasibility of developing discovery learning-based E-LKPD assessed by media experts with a feasibility of 0.79 with the feasible category and material experts were in the feasibility of 0.89 with the very feasible category and teacher assessment with a feasibility of 0.94 with the very feasible category, (2) the response of students to the discovery learning-based E-LKPD was 0.99 with the very interesting category, (3) E-LKPD based on discovery learning is stated to be able to improve student learning outcomes by obtaining an N-Gain Score of 0.78 with a high category and a percentage of 77.61 in the